AI and Digital Transformation Trends: A Systematic Review with Multi-Criteria Analysis - Soni Adiyono; Muhammad Arifin (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This research investigates the integration of Artificial Intelligence (AI) and Digital Transformation (DT) as critical enablers of Industry 4.0, highlighting their combined influence in reshaping industrial processes and enhancing operational efficiency. AI technologies, including machine learning, natural language processing, and computer vision, are driving advancements in automation, real-time decision-making, and personalized services across various industries, such as manufacturing, healthcare, and logistics. DT involves the widespread adoption of digital technologies that transform business models, stakeholder interactions, and organizational structures, working synergistically with AI to foster innovation. While existing literature often examines AI and DT in isolation, this study addresses the gap by employing a Systematic Literature Review (SLR) and Multi-Criteria Analysis (MCA) methodology to evaluate research based on academic impact, practical relevance, and sectoral readiness. The analysis reveals emerging trends such as predictive analytics, autonomous systems, and smart manufacturing, with industries like healthcare and retail showing strong adoption, while real estate and legal services remain underexplored. The research examines 46,936 Scopus records and selects 32 studies for analysis. The MCA results underscore the importance of aligning academic research with industrial needs and fostering cross-sector collaboration. Ultimately, this study bridges the gap between theory and practice, offering valuable insights for policymakers, scholars, and practitioners to strengthen competitive advantage in the digital era.